Integrated Management of White Mold on Vegetables in Florida - Mathews L. Paret; Nicholas S. Dufault; Joshua H. Freeman; Stephen M. Olson (EDIS)
PP276 provides information on what crops white mold (Sclerotinia spp.) affects in Florida and available methods of control. Includes references. Updated August 2018.